Comparative effectiveness of adrenal sparing radical nephrectomy and non-adrenal sparing radical nephrectomy in clear cell renal cell carcinoma: Observational study of survival outcomes - Nason, Gregory J. (Can Urol Assoc J, 2015)
INTRODUCTION: We compare the survival outcomes of patients with clear cell renal cell carcinoma (RCC) treated with adrenal sparing radical nephrectomy (ASRN) and non-adrenal sparing radical nephrectomy (NASRN). METHODS: We conducted an observational study based on a composite patient population from two university teaching hospitals who underwent RN for RCC between January 2000 and December 2012. Only patients with pathologically confirmed RCC were included. We excluded patients undergoing cytoreductive nephrectomy, with loco-regional lymph node involvement. In total, 579 patients (ASRN = 380 and NASRN = 199) met our study criteria. Patients were categorized by risk groups (all stage, early stage and locally advanced RCC). Overall survival (OS) and cancer-specific survival (CSS) were analyzed for risk groups. Survival analysis was performed using Kaplan-Meier curves and Cox proportional hazards regression. RESULTS: The median follow-up was 41 months (range: 12–157). There were significant benefits in OS (ASRN 79.5% vs. NASRN 63.3%; p = 0.001) and CSS (84.3% vs. 74.9%; p = 0.001), with any differences favouring ASRN in all stage. On multivariate analysis, there was a trend towards worse OS (hazard ratio [HR] 1.759, 95% confidence interval [CI] 0.943–2.309, p = 0.089) and CSS (HR 1.797, 95% CI 0.967–3.337, p = 0.064) in patients with NASRN (although not statistically significant). Of these patients, only 11 (1.9%) had adrenal involvement. CONCLUSIONS: The inherent limitations in our study include the impracticality of conducting a prospective randomized trial in this scenario. Our observational study with a 13-year follow-up suggests ASRN leads to better survival than NASRN. ASRN should be considered the gold standard in treating patients with RCC, unless it is contraindicated.